Komparasi Peramalan Permintaan Jangka Pendek untuk Pemerataan Beban Kerja di Warehouse Telkomsel Bandung - Jauhari Rahmat Gunawan; Bambang Darmawan; Wiku Larutama (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Managing high volume product flows at Warehouse Telkomsel Bandung faces challenges due to uneven workloads, as demand forecasting has not yet been implemented to account for potential inventory levels in the coming period. Using a descriptive quantitative approach and 5 Why’s analysis, this study further examined historical data compiled by the company over an 18 weeks period. As a result, Single Exponential Smoothing (SES) method was selected as the best method because it has the lowest error rate and controlled validation results. It is recommended that the company implement thi SES method and update the data periodically to maintain forecasting accuracy in the next period.